Study of respiratory disease pattern in children aged 2 months-5 years admitted in a tertiary care hospital - S. R., Raja; J., Shabin; M., Mathivanan; M., Muthu Rama Subramanian (International Journal of Contemporary Pediatrics, 2021)
Background: Acute respiratory infections (ARI) is one of the leading causes of under 5 mortality globally and in India. India accounts for 20% of deaths globally due to pneumonia. Reviewing the prevalence and profile of pneumonia admissions in a tertiary care hospital will reflect the burden in the community and thereby help to plan optimal use of resources and adopting proper preventive measures. Aim of study was to identify prevalence, various risk factors involved, morbidity and mortality of acute respiratory infections in children 2 months to 5 years old. Methods: A prospective observational study conducted at a tertiary care teaching hospital of southern Tamil Nadu, India over a period of 18 months (January 2016 to June 2017). All cases between the age group of 2 months to 5 years admitted to Paediatric department were included in the study. Demographic and clinical features were recorded. Statistical analysis was done using SPSS version 22.0. Results: A total of 2793 children were included, of which the prevalence of acute respiratory infection was 10.95% (306 children). Pneumonia was the most common diagnosis (38.5%) followed by bronchiolitis (15.3%). Mortality rate was 5.9% among the ARI cases. There was a significant influence of exclusive breast feeding and malnutrition over the morbidity and mortality of ARI cases. Conclusions: Identifying ARI cases with risk factors for developing severe and very severe pneumonia and children with risk factors for high mortality need to be referred to tertiary care centres as early as possible for better outcome.